A multi-source virtual water metabolism model for urban systems. (1st December 2020) - Zheng, Xiaogui; Huang, Guohe; Liu, Lirong; Zheng, Boyue; Zhang, Xiaoyue
Abstract: Increasing industrialization and urbanization stress on water resources in the world. It is crucial to analyze urban virtual water metabolism systems comprehensively to uncover economic water flow reduction pathways to support maintainable development. In this study, a multi-source virtual water metabolism (MVWM) model is developed for Chongqing City to facilitate distributive analysis of the interactive effects from multiple water sources on urban systems. In addition, three disaggregated types of water sources (surface water, groundwater, and other water) are examined with their distributive features in relation to virtual and physical water shortages being highlighted among multiple sectorial users. The system's health condition is monitored by integrating ecological network analysis (ENA) and input-output analysis (IOA). Results illustrate that the groundwater system in Chongqing is relatively healthy and can be exploited appropriately, while the surface water system has higher water stress. Direct water consumptions are mostly happened in primary industries, while indirect water consumptions are most likely to occur in secondary and tertiary industries. Based on ecological hierarchy analysis, Advanced Manufacturing (AM) has large pulling and driving force simultaneously, which denotes that AM is very important for the whole economic system of Chongqing. Besides, some typical industries with damaging relationships are identified based on ecological network utility analysis to alleviate water scarcity, such as construction, mining and washing of coal, as well as manufacture of foods and processing of tobacco. Graphical abstract: Image 1 Highlights: A multi-source virtual water metabolism model is developed for Chongqing City. Three disaggregated types of water sources are examined with their distributive features. Water consumption intensity and flow relationships are identified. Connections between water consumption and economy are established. Policy suggestions for water resources management are proposed based on local realities.